Immunodetection of rasP21 and c-myc oncogenes in oral mucosal swab preparation from clove cigarette smokers - Silvi Kintawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
Background: Smoking is the biggest factor for oral cavity malignancy. Some carcinogens found in cigar will stimulate epithel cell in oral cavity and cause mechanism disturbance on tissue resistance and produce abnormal genes (oncogenes). Oncogenes ras and myc are found on malignant tumor in oral cavity which are associated with smoking. Purpose: This research is to find the expression of oncogenes rasP21 and c-myc in oral mucosa epithelial of smoker with immunocytochemistry reaction. Methods: An oral mucosal swab was performed to 30 smokers categorized as light, moderate, and chain, and 10 non smokers which was followed by immunocytochemistry reaction using antibody towards oncogene rasP21 and c-myc is reacted to identify the influence of smoking towards malignant tumor in oral cavity. The result is statistically analyzed using Kruskal-Wallis test. Result: Based on the observation result of oncogene rasP21reaction, it shows that there is significant difference between non smoker group and light smoker, compared to moderate and chain smoker group (p < 0.01). On the other side, the observation result of oncogene c-myc indicates that there is no significant difference between the group of non smokers and the group of light, moderate, and chain smokers (p > 0.05). Conclusion: The higher the possibility of oral cavity malignancy and that the antibody for rasP21 oncogene can be used as a marker for early detection of oral cavity malignancy caused by smoking.